2014
DOI: 10.1108/cgij-03-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Nurse led discharge: improving efficiency, safely

Abstract: Purpose – The purpose of this paper is to demonstrate that nurse led discharge (NLD) could improve the efficiency of simple discharges from a short stay surgical ward without compromising patient safety. Design/methodology/approach – A protocol for NLD was designed and implemented. Introduction of the protocol was audited and re-audited prospectively. Findings – Introduction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…Four articles (n = 15) provided empirical data regarding the safety of using criteria to guide patient discharge. [18][19][20][21] Safety measures were described as follows: health care team agreement regarding clinical CLD protocols, staff training/preparation for CLD, patient information about CLD, patient follow-up (postdischarge), and monitoring patient readmissions following CLD. None of the studies found that readmission rates for patients discharged using CLD were increased.…”
Section: Review Question 1: Safety Of Cldmentioning
confidence: 99%
See 4 more Smart Citations
“…Four articles (n = 15) provided empirical data regarding the safety of using criteria to guide patient discharge. [18][19][20][21] Safety measures were described as follows: health care team agreement regarding clinical CLD protocols, staff training/preparation for CLD, patient information about CLD, patient follow-up (postdischarge), and monitoring patient readmissions following CLD. None of the studies found that readmission rates for patients discharged using CLD were increased.…”
Section: Review Question 1: Safety Of Cldmentioning
confidence: 99%
“…Bowen et al 19 aimed to improve the efficiency of simple discharges without compromising patient safety through a protocol developed by the health care team. This enabled the discharge of patients by nurses without further review of a physician.…”
Section: Review Question 1: Safety Of Cldmentioning
confidence: 99%
See 3 more Smart Citations